Variations for oil content and fatty acid composition in wild Arachis species: Variations for oil content and fatty acid composition in wild Arachis species - A L RATHNAKUMAR; K GANGADHARA; S K BERA; B C AJAY; G HARISH (Journal of Oilseeds Research, 2020)
Oil content and fatty acid composition of 41 wild species representing four sections of the genus Arachis were estimated. The major fatty acids observed in different wild Arachis species were palmitic, stearic, oleic, and linoleic acids. Oil content varied between 49% (A. stenosperma) to 58% (A. batizocoi). Oleic acid content was higher than linoleic acid. Oleic acid content ranged from 29.2% (A.appressipila) to 56.5% (A. stenophylla). Linoleic acid was in the range of 22.9% (A. stenophylla) to 46.7% (A.monticola). Ratio of oleic to linoleic acid ranged from 0.66 to 2.48. No significant relationship between oil content and fatty acid composition could be found.